2008
DOI: 10.1021/jp711984t
|View full text |Cite
|
Sign up to set email alerts
|

Role of Photolysis Frequency in Enhanced Selectivity and Yield for Controlled Bond Breaking in HOD

Abstract: Quantum dynamical calculations on HOD subjected to different combinations of IR and UV pulses have been made to isolate field attributes which maximize selectivity and yield in the photodissociation of the desired O-H/O-D bond. Results from IR/UV pulse combinations which provide very high selectivity and/or yield are analyzed in detail by using population transfer, probability density flow, and flux variations to obtain microdynamic details favoring selectivity and yield. Results indicate that a 2727 cm (-1) 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…This finding can be explained by the difference in masses between deuterium and proton, which results in different bond stretching frequencies when they are allowed to move on the same repulsive potential. Previous investigations on the photodissociation of HOD on its first excited-state PES gave similar results. It is important to mention that classical trajectory calculations on HOD 2+ gave the value of branching ratio 8.6, which is quite different from quantum results.…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…This finding can be explained by the difference in masses between deuterium and proton, which results in different bond stretching frequencies when they are allowed to move on the same repulsive potential. Previous investigations on the photodissociation of HOD on its first excited-state PES gave similar results. It is important to mention that classical trajectory calculations on HOD 2+ gave the value of branching ratio 8.6, which is quite different from quantum results.…”
Section: Resultssupporting
confidence: 66%
“…Influence of other initial conditions, like initial rotational and vibrational states of HOD molecule, on dissociation dynamics of HOD 2+ is yet to understand. Previous studies showed that weak-field unimolecular photodissociation dynamics of HOD strongly depends on the initial vibrational state of HOD molecule. In this article, we would like to answer the question: Does the dissociation dynamics of HOD 2+ depend on the initial vibrational state of HOD molecule as in the case of HOD photodissociation?…”
Section: Introductionmentioning
confidence: 99%
“…The method employed here is identical with that employed in our earlier investigations, and as in other previous investigations, ,,,,,, , we too have considered only the ground and first excited electronic states with bending angle frozen at its equilibrium value. Rotational motion has been neglected as we are studying events on a femtosecond scale.…”
Section: Methodsmentioning
confidence: 99%
“…Laser-assisted selective control of products from a chemical reaction is a subject of much importance and intense interest. The local mode character of the O−H and O−D bonds in HOD and availability of accurate potential energy and dipole moment surfaces has made HOD a popular candidate for detailed investigation of selective bond dissociation. The first excited 1 B 1 electronic state of HOD is purely repulsive with a saddle point barrier separating the H + O−D and H−O + D channels. Excitation to the 1 B 1 surface causes negligible change in the bending angle and use of preexcited O−H/O−D bonds in the ground electronic state with appropriate laser pulses which will deposit HOD in the desired dissociative channel on the repulsive upper surface has been an effective route to selective bond cleavage in HOD. , , ,, These features have made it possible to examine selective dissociation of O−H and O−D bonds using only the ground and first excited potential energy surfaces using reasonable UV pulses ,,, , in considerable detail and the preferential dissociation of O−H and O−D bonds in H + O−D ← H−O−D → H−O + D has served as a popular prototype for selective photodynamic control of chemical reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation